1994
DOI: 10.1136/bmj.308.6933.891
|View full text |Cite
|
Sign up to set email alerts
|

Deep venous thrombosis and occult malignancy: an epidemiological study

Abstract: Deep venous thrombosis is associated with a significantly higher frequency of malignancy during the first six months after diagnosis. Malignancies can be found with simple clinical and diagnostic methods and extensive screening is not required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
146
5
10

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(174 citation statements)
references
References 8 publications
13
146
5
10
Order By: Relevance
“…More recently, several large retrospective studies have shown an increased risk of cancer after a diagnosis of idiopathic VTE, with standardised incidence ratios of 3 -4.2 within the first 6 months (Nordstrom et al, 1994;Sorensen et al, 1998;Murchison et al, 2004). The length of time for which increased risk can be shown varies and we have shown a persistent, although declining, risk up to 2 years from VTE diagnosis (Murchison et al, 2004).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…More recently, several large retrospective studies have shown an increased risk of cancer after a diagnosis of idiopathic VTE, with standardised incidence ratios of 3 -4.2 within the first 6 months (Nordstrom et al, 1994;Sorensen et al, 1998;Murchison et al, 2004). The length of time for which increased risk can be shown varies and we have shown a persistent, although declining, risk up to 2 years from VTE diagnosis (Murchison et al, 2004).…”
mentioning
confidence: 75%
“…In view of this increased risk, there has been an interest in screening patients with idiopathic VTE for occult malignancy. Initial retrospective studies in patients with idiopathic deep vein thrombosis (DVT) suggested that most occult malignancy could be detected by routine evaluation (Nordstrom et al, 1994;Cornuz et al, 1996). However, more recent prospective studies advocate a more intensive investigative approach Piccioli et al, 2004).…”
mentioning
confidence: 99%
“…There is, however, no consensus on whether an extensive screening program for cancer may be meaningful in a subgroup of VTE patients [1][2][3]. We describe in the present study the time period of increased manifestation of cancer in VTE patients as compared to the background incidence in the Dutch population.…”
mentioning
confidence: 93%
“…Lack of ADAMTS-13 activity can be caused either by a rare hereditary deficiency or by acquired autoantibodies that specifically inhibit ADAMTS-13 function [5,6]. The majority of clinically observed adult TTP patients are immune acquired cases [3,[6][7][8][9], with patients showing detectable levels of autoantibodies to ADAMTS-13. Patients exhibiting immune acquired TTP, also termed idiopathic TTP, usually respond well to plasma exchange (PE) therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation